LIQUIDUS EQUILIBRIA OF SOME PRIMARY LUNAR AND TERRESTRIAL MELTS IN THE GARNET STABILITY FIELD - Longhi J. (My University, 1995)
Melting experiments conducted at 28 and 30 kbar on synthetic starting materials with compositions appropriate to terrestrial (depleted) and lunar mantles (undifferentiated and cumulate) show that (1) low-degree melts of mantles with lherzolitic mineral assemblages (olivine + orthopyroxene + clinopyroxene + garnet) will be (picritic) tholeiitic to transitional in character; (2) the melting equilibrium is ol + gar + cpx = opx + liq over a wide range of MgO/FeO; (3) the clinopyroxene coexisting with low-degree melts is low in CaO (~7 wt%), as predicted by Bertka and Holloway (1993); (4) the solubility of aluminous components in pyroxene is much greater than at low pressure; and (5) the CaO concentration in clinopyroxenes coexisting with olivine and garnet in various runs ranges continuously from 7 to 16 wt%.The data place the following constraints on magma genesis: (1) polybaric fractional fusion of lunar and depleted terrestrial sources with olivine, two pyroxenes, and an aluminous phase will produce pooled melts that crystallize olivine, augite, and plagioclase before low-Ca pyroxene at low-pressure (i.e., tholeiites); (2) the absence of tholeiitic lavas or cumulates on the Moon indicates high-degree melts and/or no residual aluminous phase in lunar source regions; and (3) the low-Ca clinopyroxene on the high-pressure lherzolite solidus is a super-critical clinopyroxene that appears on the anhydrous lherzolite solidus with increasing pressure when the ol + pig + aug liquidus boundary curve develops a critical end point. This critical end point terminates the high-Al2O3 end of the ol + pig + aug liquidus curve. As the critical end point migrates to the Opx-Wo join, it progressively eliminates the ol + pig + aug liquidus curve, which disappears entirely by about 20 kbar.